Noelaerhabdaceae coccolith length (mean, 5th percentile and 95th percentile) over the past 40 million years compiled from the literature - Clara T Bolton; Heather M Stoll (PANGAEA, 2025)
This dataset contains the data plotted in Figure 5 of the review paper Coccoliths as Recorders of Paleoceanography and Paleoclimate over the Past 66 Million Years by Bolton & Stoll (2025, AREPS; doi:10.1146/annurev-earth-040623-103211). It is a compilation of previously published data on Noelaerhabdaceae coccolith size (mean length and 5th and 95th percentiles where available) over the last 40 million years. The data provide insights into coccolith size evolution, of interest for paleoceanographic and micropaleontological research. Data come from a large number of DSDP/ODP/IODP, NGHP, and MD sediment cores from the Atlantic, Pacific and Indian Oceans, and values are based on (manual and automated) light microscope measurements of Noelaerhabdaceae coccoliths.